Implementation of Drill Method to Improve Forehand Stroke Skills in Table Tennis Learning - Utin Astuti; Marsuna (Jurnal Muara Olahraga, 2026)
This study aims to determine the improvement of forehand stroke skills in table tennis learning through the implementation of the drill method. This study used Classroom Action Research (CAR) which was carried out in two cycles, with stages including planning, implementation, observation, and reflection. The subjects of the study were all 21 students of grade XI IPA. The instrument used to measure the psychomotor aspect was a forehand stroke skill performance test. Data were analyzed using a percentage technique based on the level of student learning completion. The results showed that in cycle I, student learning completion reached 71.43% or 15 out of 21 students, so it did not meet the set standard of 75%. In cycle II, learning completion increased to 90.47% or 19 out of 21 students. Thus, the implementation of the drill method can improve forehand stroke skills in table tennis learning.